The effect of the "woman life freedom" protests on life satisfaction in Iran: Evidence from survey data - Mohammad Reza Farzanegan; Sven Fischer (Philipps-University Marburg, School of Business and Economics, 2025)
This study examines the effect of the "Woman, Life, Freedom" protests in Iran during the last quarter of 2022 on individual life satisfaction. To assess this impact, we use two original representative surveys conducted before and after the protests in 2022. The repeated cross-sectional dataset was generated using the same sampling approach in both surveys to ensure representativeness. Our results, based on probit regressions and an instrumental variable approach for a sample of 2,256 individuals, show that the violent protest environment had a significant negative effect on life satisfaction in Iran. To measure respondents' exposure to the protests, this study uses various indicators based on the distance of individual respondents from the protest locations. Overall, the protest environment decreased the probability of life satisfaction by 3.6 percentage points. These results remain robust when controlling for other determinants of individual life satisfaction. Moreover, we find significant heterogeneity among respondents based on gender, with the largest negative impact of the protests on life satisfaction observed among women. This negative effect is more pronounced than the impact of unemployment. Another key finding is the heterogeneous effect depending on media consumption, with international TV viewers reporting the largest decrease in life satisfaction. The mechanism underlying these effects was further explored through mediation analysis, which reveals that feelings of insecurity and increased surveillance are key mediators of the total effect.
Keywords: D74; F52; H56; I31; N15; 330; Protest; Violence; Life Satisfaction; Well-Being; Woman Life Freedom; Survey; Iran